RETRACTED: Polysaccharide IV from Lycium barbarum L. Improves Lipid Profiles of Gestational Diabetes Mellitus of Pregnancy by Upregulating ABCA1 and Downregulating Sterol Regulatory Element-Binding Transcription 1 via miR-33 - Yang, Shuli; Si, Lihui; Fan, Limei; Jian, Wenwen; Pei, Huilin; Lin, Ruixin (Frontiers in Endocrinology, 2018)
Lycium barbarum L. (LBL) has beneficial effects on gestational diabetes mellitus (GDM) but the related mechanism remains unclear. Polysaccharides of LBL (LBLP) are the main bioactive components of LBL. miR-33, ATP binding cassette transporter A1 (ABCA1) and sterol regulatory element-binding transcription (SREBF1) affect lipid profiles, which are associated with GDM risk. LBLP may exert protective against GDM by affecting these molecules. Four LBLP fractions: LBLP-I, LBLP-II, LBLP-III and LBLP-IV were isolated from LBL and further purified by using DEAE-Sephadex column. The effects of purified each fraction on pancreatic beta cells were comparatively evaluated. A total of 158 GDM patients were recruited and randomly divided into LBL group (LG) and placebo group (CG). miR-33 levels, lipid profiles, insulin resistance and secretory functions were measured. The association between serum miR-33 levels and lipid profiles were evaluated by using Spearman's Rank-Order Correlation Test. After 4-week therapy, LBL reduced miR-33 level, insulin resistance and increased insulin secretion of GDM patients. LBL increased the levels of ABCA1, high-density lipoprotein cholesterol (HDL-C) and reduced miR-33, SREBF1, low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC), triglyceride (TG) and malondialdehyde (MDA). Insulin resistance (HOMA-IR) was lower in LG than in CG, whereas insulin secretory function (HOMA-IS) was higher in LG than in CG. There was a strong positive association between miR-33 level and TG, or TC and or LDL-c, and a strong negative association between miR-33 level and HDL-c. The levels of miR-33 had negative relation with ABCA1 and positive relation with SREBF1. ABCA1 has negative relation with TG, TC and LDL-C and positive relation with HDL-C. Inversely, SREBF1 had positive relation with TG, TC and LDL-C and negative relation with HDL-C. The main bioactive compound LBLP-IV of LBL increased insulin secretion of beta cells and the levels of ABCA1, and reduced miR-33 levels and SREBF1 in beta cells. However, LBLP-IV could not change the levels of these molecules anymore when miR-33 was overexpressed or silenced. LBLP-IV had the similar effects with LBL on beta cells while other components had no such effects.. Thus, LBLP-IV from LBL improves lipid profiles by upregulating ABCA1 and downregulating SREBF1 via miR-33.